A ideia de "casa da escola" no século XIX português - Silva, Carlos Manique da (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
Throughout the 19th century, the dichotomy school/home became a structural element in the buildings designed for primary education. On the other hand, when considering the chronology under analysis, we note that the public school areas tend to close in on themselves, and do not taking advantage of their “surroundings” for educational purposes, a fact medical and pedagogical discourses are not able to truly counterbalance in their proposals for openness to the environment and nature.